Off-Classroom Mathematics Teaching and Learning Using Text-Messaging Approach - Aunzo, Rodulfo (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Text messaging is the quickest and easiest way to transmit information to anyone anytime and anywhere. This mode of communication is prevalently used even in the academic arena. In this paper, Mathematics teaching-learning has gone beyond the four walls of the classroom. Text messaging was utilized in the teaching-learning process. The teacher sent concepts and illustrative examples to the students via SMS. The students interacted with the teacher and learned a new lesson through this mode of communication. A quasi-experimental research design was utilized to establish the impact of teaching-learning mathematics beyond the four walls with the aid of Text messaging. The study revealed that the experimental group performed equally with the controlled group, which revealed that the teaching-learning mathematics beyond the fours wall with the aid of Text messaging is effective. It is because the experimental group did not undergo an actual classroom teaching-learning compared to the controlled group. Further results of the investigation are presented in this paper.